Simbolisme Budaya dan Religi dalam Desain Masjid Raya Al-Mashun Medan - Syauqi Akram; Zhafran Syawal (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
Al-Mashun Grand Mosque Medan, the design of this mosque is a representation of Malay cultural and religious symbolism in Islamic architecture in Indonesia. This mosque was founded in 1906, this mosque is a complex and multifaceted topic. The architectural design of this mosque is not only visually aesthetic, but also represents the spiritual and traditional values ​​of the local community. Analyze cultural symbolism in structures, ornaments, and decorations how each chosen detail contains philosophical and religious meaning. Islamic geometric decoration symbols in the form of calligraphic flowers, and floral shapes are used to bring religious principles and universal harmony to life. Local elements such as wood and natural stone add an authentic element. Elements of cultural symbolism, it can be understood how detailed the exterior and interior design is with the identity of the local people of North Sumatra, with this article to sharpen the understanding of cultural symbolism in the design.